The Added Worker Effect for Married Women in Australia† - Gong, X (My University, 2011)
This article investigates the labour supply responses of married women in Australia to their partners’ involuntary job loss. We study women’s labour market activities in the periods before and after their partners’ job loss. We find a significant added worker effect (AddWE) in terms of increased full-time employment and working hours. The findings also suggest that it is harder for the female partners of men who have recently lost jobs to enter the labour market than it is for those already working to increase their working hours to compensate for lost income incurred by their partners’ job loss. The effect is persistent; one year after the partners’ job loss, women would still like to work more hours than they actually work. These findings suggest that marriage plays a risk-sharing role through the AddWE in Australia.
Keywords: Gender -- Female; Employment -- Exit from employment (Retirement/Redundancy); Employment -- Labour force participation; Gender; Labour market; Ageing; Gender; Employment; Exit from employment (Retirement/Redundancy); Female; Labour force participation; Gender; Ageing; Employment and unemployment